Cost-analysis model of colonoscopy preparation using split-dose reduced-volume oral sulfate solution (OSS) and polyethylene glycol with electrolytes solution (PEG-ELS). (2nd April 2016) - Huynh, Lynn; Yermakov, Sander; Davis, Matthew; Campbell, Romaine; Cleveland, Mark; Farraye, Francis A.; Yenikomshian, Mihran
Abstract: Objective: The study aimed to (1) develop a cost model for colonoscopy preparation among patients referred for colonoscopy using split-dose reduced-volume oral sulfate solution (OSS) and generic polyethylene glycol with electrolytes solution (PEG-ELS), (2) examine cost savings associated with OSS vs PEG-ELS, and (3) assess the robustness of the cost model. Methods: Efficacy of each agent was based on the results of a 541-patient clinical trial comparing OSS to PEG-ELS. Cleansing agent and colonoscopy procedure costs were calculated from OptumHealth Reporting & Insights claims data for 2010–Q12013. In the model, patients' colonoscopies were tracked over a 25 or 35 year time period until the patients reached age 75. The difference per patient per year (PPPY) in total cleansing agent and colonoscopy procedure costs over the time horizon between the OSS and PEG-ELS cohort was calculated. One-way sensitivity analyses were conducted to test the robustness of the cost model. Results: The model showed lower cost for OSS patients over the time horizon. Total PPPY costs were 280.34 for the OSS cohort and 296.36 for the PEG-ELS cohort, resulting in a cost saving of 16.01 PPPY for the OSS cohort. This was due primarily to OSS patients having fewer colonoscopies (OSS: 0.158 vs PEG-ELS: 0.170 PPPY). Over the time horizon, cost savings of 4 763 335 were observed among 10, 000 OSS patients. Cost savings switched from OSS to PEG-ELS cohort in four cases: (1) base-case cost of a completed colonoscopy decreased by 75%, (2) base-case cost of OSS increased to over 143 per usage, (3) all non-completers were lost to follow-up, and (4) OSS bowel preparation quality dropped below PEG-ELS to 70%. Conclusions: From a payer's perspective, the model showed that the use of OSS as the cleansing agent resulted in potential cost savings compared with PEG-ELS. Cost savings under OSS remained under various sensitivity analyses.